Development and Evaluation of Real-Time Reverse Transcription Recombinase Polymerase Amplification Assay for Rapid and Sensitive Detection of West Nile Virus in Human Clinical Samples - Tomar, Priyanka Singh; Kumar, Sanjay; Patel, Sapan; Kumar, Jyoti S. (Frontiers in Cellular and Infection Microbiology, 2021)
West Nile virus (WNV) causes West Nile fever and encephalitis worldwide. Currently, there are no effective drugs or vaccines available in the market to treat WNV infection in humans. Hence, it is of paramount importance to detect WNV early for the success of the disease control programs and timely clinical management in endemic areas. In the present paper, we report the development of real-time reverse transcription recombinase polymerase amplification (RT-RPA) assay for rapid and real-time detection of WNV targeting the envelope (env) gene of the virus. The RPA reaction was performed successfully at 39°C for 15 min in a real-time thermal cycler. The sensitivity of this assay was found similar to that of the quantitative real-time RT PCR (RT-qPCR) assay, which could detect 10 copies of the gene. The efficacy of the assay was evaluated with a panel of 110 WN suspected human samples showing the signs of retinitis, febrile illness and acute posterior uveitis. In comparison with RT-qPCR, RT-RPA showed a specificity of 100% (CI, 95.07–100%) and sensitivity of 96.15% (CI, 80.36–99.90%) with a negative (NPV) and positive predictive value (PPV) of 98.65 and 100%, respectively. The level of agreement between RT-RPA and reference RT-qPCR assay was shown to be very high. The turnaround time of real-time RPA assay is about 10-20 times faster than the RT-qPCR, which confirms its utility in the rapid and sensitive diagnosis of WNV infection. To the best of our knowledge, this is the first report which deals with the development of real-time RT-RPA assay for simple, rapid, sensitive, and specific detection of WNV in human clinical samples. The present RT-RPA assay proves to be a powerful tool that can be used for the rapid diagnosis of a large number of patient samples in endemic settings.